The contribution of “Kejogjakartaan” values in higher education curricula to promoting sustainable lifestyle - Taqiyya Ken Afuw (Journal of Character and Environment, 2026)
Background: Environmental problems such as climate change remain a global challenge, requiring socio-cultural approaches to support environmental sustainability. Local wisdom provides important values for promoting sustainable behavior. The Special Region of Yogyakarta initiated the Kejogjakartaan Special Education program (PKJ) to integrate philosophical values into education. However, previous studies have rarely examined how Kejogjakartaan values, including Hamemayu Hayuning Bawana, Sangkan Paraning DumadiH, and Manunggaling Kawula Gusti, are integrated into higher education curricula. This study aims to analyze the integration of these values and evaluate their contribution to students’ sustainable lifestyles. Methods: This qualitative study employed documentation analysis and in-depth interviews. Data sources included the PKJ Main Book, PKJ Guidebook for Higher Education, UNY 2025 Curriculum Guideline, course syllabus, lesson plans, and interviews with lecturers at Yogyakarta State University. Data were analyzed using Traditional Ecological Knowledge (TEK), Education for Sustainable Development (ESD), and Value-Belief-Norm (VBN) frameworks. Findings: The results indicate that Kejogjakartaan philosophical values have strong potential to encourage sustainable lifestyles, particularly Hamemayu Hayuning Bawana. However, their curriculum integration remains limited, as the values are mainly presented as discussion materials without being translated into learning outcomes or behavioral assessments. Three major barriers were identified: knowledge transmission barriers, curriculum design limitations, and inconsistent environmental messages within the campus environment. Internalization has reached the level of values and beliefs but has not yet developed into personal norms and concrete behavioral changes. Conclusion: The successful integration of local philosophical values requires alignment between lived knowledge transmission, applicative curriculum design, and supportive campus environments. Without these elements, philosophical values may remain conceptual and fail to influence student behavior. Novelty/Originality of this article: This study provides an integrative analysis of Kejogjakartaan philosophical values in higher education using TEK, ESD, and VBN perspectives, highlighting the gap between cultural knowledge, curriculum implementation, and sustainable behavioral transformation.